Price Forecasting and Hedging Methods in an Enterprise - Sokołowska, Ewelina (Prognozowanie cen i zastosowanie hedgingu w przedsiębiorstwie, 2010)
The hedging is an effective method in enterprises of the great scale of action, operating in conditions of the keen competition, narrow margins as well as the high exposition on risk. The main aim of his article is introduction of hedging as the effective method of assessing prices in the enterprise. The future contracts are derivative instruments which enable to secure the future prices of goods and services. The article is illustrated by examples from the agriculture market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 136-144
Keywords: price forecasting; hedging; derivatives